Ground Surface Quality Assessment Using P-wave Velocity from 2-D Seismic Refraction Method - Fadhli*, Zul; Anda, Sabrian Tri; Syukri, Muhammad; Karmel, Moehammad Ediyan Raza; Tutifla, Alfi Sunny; Hasibuan, Purwandy; Safitri, Rini (Graduate School of Universitas Syiah Kuala, 2022)
A good strength level of the ground surface is the main concern in an area with rapid housing infrastructure development,such as Baitussalam district-Aceh Besar, Indonesia. A seismic refraction method was applied with three similar profile lines using PASI 16S 24P equipment and 10 Hz vertical geophones to identify the sub-surface layer. The result was processed using Winsism software and Surfer 8. The results of seismic refraction were deduced and correlated with conventional geotechnical investigation obtained by a previous study. The results of 3 survey lines show that the area has two main layers. The first layer was interpreted as overburden (soil and clayey sand) with a compressional wave velocity (Vp) value of fewer than 1.8 km/s. The second layer produces a high velocity of more than 2 km/s. This second layer is interpreted as highly to moderately weathered rock. The results of seismic refraction surveys of the present study suggest a reasonably good correlation with the standard penetration test (SPT) and rock quality designation (RQD) obtained in the previous investigation. The strength level of the second layer showed N-SPT of 65 and RQD of at least 50%.